2004
DOI: 10.1088/0957-4484/15/9/036
|View full text |Cite
|
Sign up to set email alerts
|

Electron holographic studies of irradiation damage in BaTiO3

Abstract: Using an electron holographic technique, we investigated the charging-up phenomena of BaTiO3 particles under electron beam irradiation. BaTiO3 particles were confirmed to be charged up by electron irradiation just after insertion in a transmission electron microscope (TEM). However, the amount of the electric charge induced by electron irradiation was found to decrease by further irradiation in a TEM. After irradiating for 1.5 h, about half of the electrical charge was lost compared with that in the initial s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…It has been confirmed by electron holographic technique that BaTiO 3 particles can be charged up by electron irradiation right after the sample is exposed to the electron beam [198]. Most interestingly, the amount of induced electric charge decreases with increasing electron irradiation.…”
Section: Type II Damage: Phase Transformationmentioning
confidence: 91%
“…It has been confirmed by electron holographic technique that BaTiO 3 particles can be charged up by electron irradiation right after the sample is exposed to the electron beam [198]. Most interestingly, the amount of induced electric charge decreases with increasing electron irradiation.…”
Section: Type II Damage: Phase Transformationmentioning
confidence: 91%
“…As the new nanostructures have been mainly studied by transmission electron microscopy, important research into electron irradiation effects on the nanostructures has been conducted using novel in situ characterization techniques. Yamamoto et al [13], reported the modification of the conductivity in an insulating BaTiO 3 using electron holographic studies of irradiated sample in a transmission electron microscope (TEM). The stability and the crystallization of amorphous alloys by electron irradiation have also been studied in situ [14].…”
Section: Introductionmentioning
confidence: 99%
“…[24] Without ion beam milling, the surface of annealed BaTiO 3 nanocrystals prepared in the current work stays highly resistant and electrostatic charging can be significant. [28] While both elastic and inelastic electron-atom interactions may participate in the amorphization process by generating oxygen vacancies within the nanocrystal, the following features are better explained in terms of oxygen vacancy migration under the e-beam induced electric field. i) The region subject to electrostatic charging can be larger than the e-beam illuminated area by means of ion migrations, resulting in a larger amorphized area within a BaTiO 3 nanocrystal than the e-beam illuminated area when exposed to high dose rates as shown in Figures 1 and 4. ii) The migration of oxygen vacancies is a dynamic process and local oxygen vacancy content can vary with time, so a reversible crystalline/amorphous transition can exist in the illuminated region as noticed in Figure 6. iii) The electric field direction is radial and consistent with the outward growth direction of the amorphized region shown in Figure 6c.…”
Section: (7 Of 9)mentioning
confidence: 99%
“…Without ion beam milling, the surface of annealed BaTiO 3 nanocrystals prepared in the current work stays highly resistant and electrostatic charging can be significant. [ 28 ] While both elastic and inelastic electron‐atom interactions may participate in the amorphization process by generating oxygen vacancies within the nanocrystal, the following features are better explained in terms of oxygen vacancy migration under the e‐beam induced electric field. i) The region subject to electrostatic charging can be larger than the e‐beam illuminated area by means of ion migrations, resulting in a larger amorphized area within a BaTiO 3 nanocrystal than the e‐beam illuminated area when exposed to high dose rates as shown in Figures 1 and 4.…”
Section: Mechanisms Of E‐beam Induced Amorphizationmentioning
confidence: 99%